Daikenchuto (TU‐100) Suppresses Tumor Development in the Azoxymethane and APCmin/+ Mouse Models of Experimental Colon Cancer. (12th October 2016) - Hasebe, Takumu; Matsukawa, Jun; Ringus, Daina; Miyoshi, Jun; Hart, John; Kaneko, Atsushi; Yamamoto, Masahiro; Kono, Toru; Fujiya, Mikihiro; Kohgo, Yutaka; Wang, Chong‐Zi; Yuan, Chun‐Su; et al.
Abstract : Chemopreventative properties of traditional medicines and underlying mechanisms of action are incompletely investigated. This study demonstrates that dietary daikenchuto (TU‐100), comprised of ginger, ginseng, and Japanese pepper effectively suppresses intestinal tumor development and progression in the azoxymethane (AOM) and APC min/+ mouse models. For the AOM model, TU‐100 was provided after the first of six biweekly AOM injections. Mice were sacrificed at 30 weeks. APC min/+ mice were fed diet without or with TU‐100 starting at 6 weeks, and sacrificed at 24 weeks. In both models, dietary TU‐100 decreased tumor size. In APC min/+ mice, the number of small intestinal tumors was significantly decreased. In the AOM model, both TU‐100 and Japanese ginseng decreased colon tumor numbers. Decreased Ki‐67 and β‐catenin immunostaining and activation of numerous transduction pathways involved in tumor initiation and progression were observed. EGF receptor expression and stimulation/phosphorylation in vitro were investigated in C2BBe1 cells. TU‐100, ginger, and 6‐gingerol suppressed EGF receptor induced Akt activation. TU‐100 and ginseng and to a lesser extent ginger or 6‐gingerol inhibited EGF ERK1/2 activation. TU‐100 and some of its components and metabolites of these components inhibit tumor progression in two mouse models of colon cancer by blocking downstream pathways of EGF receptor activation. Copyright © 2016 John Wiley & Sons, Ltd.